ANALYSIS OF THE EFFICIENCY OF ION EXCHANGE, DEPENDING ON THE DEGREE OF WASTEWATER CONTAMINATION - Dymnikova, O. V.; Krivoblotskaya, D. A.; Dorjderem, B. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2017)
The article considers the influence of various parameters on the efficiency of ion exchange process to improve the quality of softening and desalination of water. It presents the dependence of the process on the duration and different characteristics of solutions by varying the concentration and nature of solute. On the basis of the results obtained the authors drawn a conclusion about the applicability of ion exchange for water purification.